2020
DOI: 10.1103/physrevd.102.071701
|View full text |Cite
|
Sign up to set email alerts
|

Implications for new physics from a novel puzzle in B¯(s)0

Abstract: Recently, the standard model predictions for the B-meson hadronic decays,B 0 → D ðÃÞþ K − and B 0 s → D ðÃÞþ s π − , have been updated based on the QCD factorization approach. This improvement sheds light on a novel puzzle in the B-meson hadronic decays: there are mild but universal tensions between data and the predicted branching ratios. Assuming the higher-order QCD corrections are not huge enough to solve the tension, we examine several new physics interpretations of this puzzle. We find that the tension c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 54 publications
(67 reference statements)
1
24
0
Order By: Relevance
“…In each plot the black dotted line shows the result for the fit (i). to be 1 TeV as a reference [9]:…”
Section: Global Analysismentioning
confidence: 99%
“…In each plot the black dotted line shows the result for the fit (i). to be 1 TeV as a reference [9]:…”
Section: Global Analysismentioning
confidence: 99%
“…In this paper, as an alternative, we shall examine possible NP interpretations of the deviations observed; for recent discussions along this line, see refs. [40][41][42][43][44][45].…”
Section: Jhep10(2021)235mentioning
confidence: 99%
“…As emphasized already in ref. [51], such an NLO analysis in the NP sector is crucial for reducing certain unphysical scale and renormalization scheme dependences present in the absence of these O(α s ) corrections [40][41][42][43][44][45]. It is numerically found that, under the combined constraints from the current experimental data, the deviations observed could be well explained at the 1σ level by the NP four-quark operators with γ µ (1 − γ 5 ) ⊗ γ µ (1 − γ 5 ) structure, and also at the 2σ level by the operators with (1 + γ 5 ) ⊗ (1 − γ 5 ) and (1 + γ 5 ) ⊗ (1 + γ 5 ) structures.…”
Section: Jhep10(2021)235mentioning
confidence: 99%
“…(s) → D + (s) π − [5][6][7][8]. Such decays are dominated by colour-allowed tree topologies JHEP10(2021)223…”
Section: Introductionmentioning
confidence: 99%